Changes in treatment patterns and impact of radiotherapy for early stage diffuse large B cell lymphoma after Rituximab: A population-based analysis. Issue 1 (July 2016) - Haque, Waqar; Dabaja, Bouthaina; Tann, Anne; Khan, Mohammad; Szeja, Sean; Butler, E. Brian; Teh, Bin S.
Abstract: Purpose: Use of Rituximab for diffuse large B cell lymphoma (DLBCL) has improved outcomes and led to further questions regarding the benefit of consolidative radiation therapy (RT). This study sought to determine changes in RT utilization following the incorporation of Rituximab for treatment of early stage DLBCL and to examine survival outcomes. Materials/methods: We included patients in the Surveillance, Epidemiology, and End Results database, diagnosed with Stage I–II DLBCL between 1992 and 2011. Linear regression was performed to determine rate of RT utilization over time during the pre- and post-Rituximab eras (1992–2001 vs. 2002–2011). Kaplan–Meier and Cox Regression were performed to compare overall survival (OS) for patients treated with or without RT. Propensity-score matching was used to compare survival outcomes to account for indication bias. Results: 34, 680 patients met the specified criteria. RT utilization was 35.2% in the pre-Rituximab era and 29.9% in the post-Rituximab era ( ​P  < 0.001). Linear regression revealed that in the pre-Rituximab era the slope of the best fit line for RT utilization by year was positive ( m  = 0.01, ​P  = 0.0046), while the slope was negative in the post-Rituximab era ( m  = −0.008, ​P  = 0.0102). RT use was associated with improved OS in both the pre-Rituximab era (hazard ratio [HR] = 0.797; 95% confidence interval [CI] 0.756–0.841) and the post-Rituximab era (HR = 0.745; 95% CI 0.702–0.789). Propensity-score matched analysis confirmed that RT use improved OS in the pre-Rituximab era (HR = 0.844; 95% CI 0.793–0.897) and post-Rituximab era (0.754; 95% CI 0.703–0.809). Conclusion: RT utilization has decreased following incorporation of Rituximab for first line treatment of DLBCL. RT use is associated with improved OS in both pre- and post-Rituximab eras, suggesting that RT should continue to be used for management of early stage DLBCL, even in the era of Rituximab.